UTILISATION OF INNOVATIVE PEDAGOGICAL STRATEGIES: A CROSS-SECTIONAL SURVEY IN VOCATIONAL AND TECHNICAL EDUCATION IN TERTIARY INSTITUTIONS (NAU Journal of Technology and Vocational Education, 2024)
The study sought to determine the extent of utilisation of innovative pedagogical strategies for teaching of vocational and technical education courses in tertiary institutions in Delta State. Two research questions were raised for the study and four null hypotheses were tested. Descriptive survey research design was adopted. The entire population of 189 VTE lecturers in the five public owned tertiary institutions in Delta State was studied without sampling. A structured and questionnaire which was validated by experts was used for data collection. Cronbach alpha was used to measure the internal consistency which yielded an overall reliability co-efficient of 0.87. The researchers administered the instrument with five research assistants using direct method to the respondents. Mean and standard deviation were used for answering the research questions and t-test was used for testing the null hypotheses at 0.05 level of significance. The study revealed that VTE lecturers slightly utilised activity-based and interactive pedagogical strategies for teaching vocational and technical education courses in tertiary institutions in Delta State. The study concluded that VTE lecturers, irrespective of their gender and years of teaching experience slightly utilized activity-based pedagogical strategies and interactive pedagogical strategies when teaching VTE courses in tertiary institutions. Among others, it was recommended that professional conferences and in-service seminars should be organized for VTE lecturers to update their instructional competency on the utilisation of activity-based and interactive pedagogical strategies. This would increase VTE lecturers’ instructional efficacy and be more open to use activity-based and interactive pedagogical strategies for teaching VTE courses in tertiary institutions.
Keywords: Vocational and technical education; innovative pedagogical strategies; activity-based strategies; interactive strategies